Determination of celecoxib in human plasma by liquid chromatography-tandem mass spectrometry - Ptáček, Pavel; Klíma, Josef; Macek, Jan (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2012)
A liquid chromatography-electrospray tandem mass spectrometry method was developed and validated to quantitate celecoxib in human plasma. The assay was based on protein precipitation with methanol and liquid chromatography on a C₁₈ column (55 mm × 2 mm, 3 μm), the mobile phase consisted of methanol-10 mM ammonium acetate (75:25, v/v). Quantification was performed by mass spectrometry in the multiple reaction monitoring mode with negative electrospray ionization at m/z 380→316 and 384→320 for celecoxib and the internal standard celecoxib-D₄, respectively. The lower limit of quantitation was 7.0 ng/ml using 0.1 ml of plasma and linearity was demonstrated up to 1800 ng/ml. Intra-assay and inter-assay precision expressed by relative standard deviation was less than 4% and inaccuracy did not exceed 6% at all levels. The assay was applied to the analysis of samples from a pharmacokinetic study.
Keywords: Adolescent; Cyclooxygenase 2 Inhibitors; Male; celekoxib; mladý dospělý; Tandem Mass Spectrometry; Middle Aged; Young Adult; pyrazoly; Sulfonamides; Plasma; Celecoxib; Chromatography, High Pressure Liquid; mužské pohlaví; Adult; tandemová hmotnostní spektrometrie; inhibitory cyklooxygenasy 2; mladiství; krevní plazma; sulfonamidy; vysokoúčinná kapalinová chromatografie; dospělí; hmotnostní spektrometrie s elektrosprejovou ionizací; lidé středního věku; Spectrometry, Mass, Electrospray Ionization; lidé; Humans; Pyrazoles